Beyond Borders: Identity, Migration, and Belonging in Abdulrazak Gurnah's Gravel Heart (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2026)
Contemporary migration has transformed the ways individuals negotiate identity, belonging, and cultural affiliation across national and transnational spaces. Rather than merely representing physical movement, migration entails complex processes of cultural adaptation, displacement, and identity reconstruction. This paper examines the dynamics of deculturation in Abdulrazak Gurnah's Gravel Heart through the theoretical framework of transculturalism, with particular emphasis on transculturation. It investigates how the novel's migrant characters navigate the tensions between their inherited cultural identities and the dominant cultures they encounter, asking whether migration results in the erosion, transformation, or reconfiguration of cultural identity. Through a qualitative textual analysis, the study demonstrates that deculturation in Gravel Heart does not signify the complete loss of one's cultural heritage; rather, it involves the selective abandonment, negotiation, and redefinition of cultural practices in response to new social and cultural environments. The analysis further reveals that this process often generates psychological distress, alienation, and identity fragmentation, while simultaneously creating opportunities for the emergence of hybrid identities and transcultural belonging. The paper argues that Gurnah presents cultural "in-betweenness" not as a condition of cultural deficiency but as a dynamic space where migrants continuously negotiate multiple identities. It concludes that transcultural hybridity provides a more sustainable framework for understanding migrant experiences than rigid notions of cultural assimilation or cultural loss, thereby contributing to contemporary debates in postcolonial migration studies and transcultural theory
Keywords: transculturalism, transculturation, deculturation, migration; identity, belonging, hybridity